A STEM Course Analysis During COVID-19: A Comparison Study in Performance and Affective Domain of PSTs Between F2F and F2S Flipped Classroom - Jeong, Jin Su; González-Gómez, David (Frontiers in Psychology, 2021)
Due to the worldwide COVID-19 pandemic, university education has a significant challenge that requires significant adaptation to virtual and online education. Here, a fruitful flipped methodology with increased popularity can support to adapt and improve current pandemic situations. This research presents a comparison of two different instruction situations with an identical teaching methodology, face-to-face (F2F) and face-to-screen (F2S) flipped methodology in terms of students’ performance and affective domain in a science, technology, engineering and mathematics (STEM) course. It was considered and designed as a randomization examination with 132 pre-service teachers (PSTs), respectively 68 and 64 PSTs for each group. Frist group before the pandemic was applied by F2F flipped classroom and second group after the pandemic was applied by F2S flipped classroom. The results after pertaining various data analyses of class activities and questionaries showed that performance had been improved for both groups towards the course. Besides, F2F had a significant difference in PSTs’ emotion and perception towards the course and created classes more interactive. The mean score values students’ emotion and perception between two groups showed that the difference between these mean values were significant, suggesting a very large effect. Particularly, the effect size (ES) showed that positive emotions were more significant different variables and the items Q7 to Q9 of questionnaires indicated more significant different perceptions for both F2F and F2S after completing the course. Finally, the principal component analysis (PCA) test described that F2F answers were located mainly in the positive emotion, while F2S answers were grouped in the negative emotion, while no differences were observed for PSTs perceptions to the flipped methodology. Consequently, although F2F to F2S transition was an effective process, instructors and PSTs faced difficulties in the platform usage for online lectures reflecting emotions’ results in F2S group. Thus, while solving the problems raised, it will allow PSTs to be more interacted in virtual and online context for their future implementation having active instruction methodology and educating future students to teach STEM contents.